2017
DOI: 10.1007/s10571-017-0479-z
|View full text |Cite
|
Sign up to set email alerts
|

Neurons Internalize Functionalized Micron-Sized Silicon Dioxide Microspheres

Abstract: Microparticles have potential as neuron-specific delivery platforms and devices with many applications in neuroscience, pharmacology and biomedicine. To date, most literature suggests that neurons are not phagocytic cells capable of internalizing microparticles larger than 0.5 microns. We report that neurons transport fluorescently labeled silica microspheres with diameters of 1–2 microns into neurons in vitro and in rat brain without having overt effects on cell viability. Using flow cytometry, fluorescence a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…Depending on the cell-surface charge and hydrophobicity, surface functional groups can affect particle attachment and internalization into cells. 37 Our results may indicate that interactions between the particle surface and cell membrane are necessary, but not sufficient for ROS production and cytotoxicity.…”
Section: ■ Results and Discussionmentioning
confidence: 76%
See 1 more Smart Citation
“…Depending on the cell-surface charge and hydrophobicity, surface functional groups can affect particle attachment and internalization into cells. 37 Our results may indicate that interactions between the particle surface and cell membrane are necessary, but not sufficient for ROS production and cytotoxicity.…”
Section: ■ Results and Discussionmentioning
confidence: 76%
“…Furthermore, our data indicated that surface carboxylation and BSA coating decreased cytotoxicity without affecting attachment to the cell surface (Figures C and S9). Depending on the cell-surface charge and hydrophobicity, surface functional groups can affect particle attachment and internalization into cells . Our results may indicate that interactions between the particle surface and cell membrane are necessary, but not sufficient for ROS production and cytotoxicity.…”
Section: Results and Discussionmentioning
confidence: 85%